Effect of external magnetic field on impact strength and hardness of weld of shielded metal arc welding process. (2021) - Agrawal, Manoj Kumar; Singh, Rudra Pratap
Abstract: Shielded metal arc welding process is effectively used to weld different metallic plates with a good quality of the joint. The external parallel magnetic field spreads the molten material of electrode on somewhat larger surface area and can be utilized to improve some required properties of the weld obtained. Generally the machine elements are subjected to sliding motion or impact loads for which hardness and impact strength of the members should be sufficient to bear the loads without failure. The present work aims to find out the effect of external parallel magnetic field on hardness and impact strength of weld in shielded metal arc welding process. All other input welding process parameters like welding current, welding voltage, welding speed, feed rate, diameter and angle of electrode etc. were kept at constant values. After experiments it was observed that the hardness and impact strength both enhance with the enhancement of external parallel magnetic field.